Fully Distributed Edge-Based Dynamic Event-Triggered Control for Multiple Quadrotors - Wang, Hao; Shan, Jinjun; Alkomy, Hassan (IEEE/ASME transactions on mechatronics, 2024)
This article investigates the fully distributed event-based time-varying formation control problem for multiple quadrotors with unknown perturbations, input saturation, and switching topologies. A novel adaptive dynamic event-triggered scheme is first formulated to alleviate the communication burden and reduce the resources consumption. Meanwhile, online triggering parameters and dynamic thresholds with updating laws associated with each edge are introduced so that the control protocol can be developed in a fully distributed way and the unnecessary communication can be further reduced for the leader-follower multiquadrotor system with switching topologies without sacrificing the tracking performance. Then, a fully distributed robust formation control protocol using the low gain feedback technique is developed to guarantee the time-varying formation of multiple quadrotors subject to unknown perturbations and input saturation without requiring global information. Furthermore, sufficient conditions are derived to ensure the asymptotic convergence of the formation error and Zeno-freeness. Hardware experiments are conducted to verify the efficiency of the designed controller.